Seroprevalensi Positif Sistiserkosis pada Babi Hutan di Kabupaten Way Kanan, Provinsi Lampung (POSITIVE SEROPREVALENCE OF WILD BOAR CYSTICERCOSIS IN WAY KANAN DISTRICT, LAMPUNG PROVINCE) - Yulianto, Heri; Satrija, Fadjar; Lukman, Denny Widaya; Sudarwanto, Mirnawati (Jurnal Veteriner; Vol 16 No 2 (2015), 2015)
Wild boar is also an intermediate host of Taenia solium, besides domestic pig which is the mainsource of Cysticercus infection in human. Cysticercosis in wild boar has not been reported in Indonesia.The aim of this study was to determine wild boar’s cysticercosis in Way Kanan District. One hundred serasamples consisting of 41 male wild boars and 59 female wild boars were collected. Eighty seven of boarscome from Banjit Subdistrict, while 13 of wild boars come from Blambangan Umpu Subdistrict in WayKanan District. The serum were tested serologically to determine antigen of parasite cycles. The test usedmonoclonal antibody-base sandwich Enzyme-Linked Immunosorbent Assay (Moab-ELISA). There is asero positive reaction of cysticercosis(1%) which is female wild boar from Banjit sub district. Controllingof meat inspection should be conducted to prevent cysticercosis transmission to human.
Keywords: wild boar, cysticercosis, Way Kanan District